2010
DOI: 10.1074/jbc.m110.155259
|View full text |Cite
|
Sign up to set email alerts
|

The Cystic Fibrosis Transmembrane Conductance Regulator Impedes Proteolytic Stimulation of the Epithelial Na+ Channel

Abstract: Cystic fibrosis (CF) is caused by mutations in the CF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 46 publications
4
81
0
Order By: Relevance
“…Besides its previously described roles in the modulation of airway inflammation, mucus hypersecretion, bacterial killing, and proteolytic lung and immune cell damage [32,[39][40][41][42], NE can activate ENaC by proteolytic cleavage and removal of ''inhibitory'' segments, probably leading to a conformational change of the channel that improves its conductivity for Na + [43,44]. Interestingly, a recent study showed that wild-type CFTR, but not DF508, interacts with ENaC in the plasma membrane of airway epithelial cells and, thus, may impede the proteolytic stimulation of ENaC by NE and potentially other extracellular proteases released by inflammatory cells [45,46]. These results suggest that lack of this ''anti-proteolytic'' function of CFTR may contribute to increased Na + absorption in chronically inflamed CF airways, and may explain why ENaC-mediated Na + transport was not elevated in newborn CF pigs prior to the onset of chronic neutrophilic airway inflammation [36].…”
Section: Airway Proteases Aggravate Basic Cf Ion Transport Defectmentioning
confidence: 99%
“…Besides its previously described roles in the modulation of airway inflammation, mucus hypersecretion, bacterial killing, and proteolytic lung and immune cell damage [32,[39][40][41][42], NE can activate ENaC by proteolytic cleavage and removal of ''inhibitory'' segments, probably leading to a conformational change of the channel that improves its conductivity for Na + [43,44]. Interestingly, a recent study showed that wild-type CFTR, but not DF508, interacts with ENaC in the plasma membrane of airway epithelial cells and, thus, may impede the proteolytic stimulation of ENaC by NE and potentially other extracellular proteases released by inflammatory cells [45,46]. These results suggest that lack of this ''anti-proteolytic'' function of CFTR may contribute to increased Na + absorption in chronically inflamed CF airways, and may explain why ENaC-mediated Na + transport was not elevated in newborn CF pigs prior to the onset of chronic neutrophilic airway inflammation [36].…”
Section: Airway Proteases Aggravate Basic Cf Ion Transport Defectmentioning
confidence: 99%
“…The mechanism underlying this functional interaction is, however, controversial, having been variously attributed to changes in intracellular chloride affecting ENaC activity (25, 54, 230), through changes in electrical driving force (73,181,202), to technical issues surrounding efficiency of voltage clamping (282). CFTR and ENaC may directly interact, based on evidence obtained from planar lipid bilayer and fluorescence resonance energy transfer (FRET) studies (37, 39), and from studies demonstrating that wild-type, but not ⌬F508-CFTR, protects ENaC from proteolytic cleavage, thereby limiting the number of channels in the highly active cleaved ENaC pool (147). Wild-type CFTR may also restrict the activity of ENaC by limiting ENaC expression and trafficking to the surface, an effect that was not observed in cells overexpressing ⌬F508-CFTR (331).…”
Section: Conditions Associated With Enac Hyperactivity: Hypertensionmentioning
confidence: 99%
“…Recently, Gentzsch et al (20) showed that CFTR coimmunoprecipitates with ENaC and inhibits its activity by decreasing proteolysis of its extracellular domains. However, these studies were conducted either in Xenopus oocytes with heterologous expression of ENaC and CFTR or in cultured human bronchial cells expressing native ENaC and CFTR.…”
mentioning
confidence: 99%
“…It functions as a cAMP-regulated Cl Ϫ channel (2) and controls other ion conductive pathways including epithelial Cl Ϫ and Na ϩ channels (53,58). Putative mechanisms responsible for the negative regulation of ENaC by CFTR (34) include physical interaction between these two proteins, higher levels of intracellular Cl Ϫ , and CFTR inhibition of ENaC subunits cleavage by proteases (6,7,20,36).…”
mentioning
confidence: 99%